2021
DOI: 10.3389/fpubh.2021.607911
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Outdoor Activity and Screen Exposure on Risk of Preschool Myopia: Findings From Longhua Child Cohort Study

Abstract: Evidence regarding screen use and outdoor activity during very early childhood (i. e., from aged 1 to 3 years) and their potential combined links to the later preschool myopia is limited. This information is needed to release effective public health messages and propose intervention strategies against preschool myopia. We collected information regarding very early childhood screen use, outdoor activity and the kindergartens vision screenings of 26,611 preschoolers from Longhua Child Cohort Study by questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 54 publications
1
34
0
1
Order By: Relevance
“…A recent meta-analysis revealed that smart device screen time alone (OR 1.26) or in combination with computer use (OR 1.77) was significantly associated with myopia in children and young adults (aged 3 months to 33 years). Huang et al reported the possibility that impact of screen exposure during early childhood on preschool myopia could be diminished by outdoor time for children whose parents have myopia ( 31 ). We therefore adjusted for age, gender, parental myopia, and screen time as well as outdoor time in our multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis revealed that smart device screen time alone (OR 1.26) or in combination with computer use (OR 1.77) was significantly associated with myopia in children and young adults (aged 3 months to 33 years). Huang et al reported the possibility that impact of screen exposure during early childhood on preschool myopia could be diminished by outdoor time for children whose parents have myopia ( 31 ). We therefore adjusted for age, gender, parental myopia, and screen time as well as outdoor time in our multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et.al. reported that exposure to fixed screen devices [adjusted odds ratio (AOR) = 2.66] and mobile screen devices (AOR = 2.66) during the early life years (1–3 years) was associated with preschool myopia ( 31 ). The World Health Organization recommends <1 h of screen time per day for preschoolers, but our results showed that 38.6% of children were exposed to more than 1 h of screen time.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 32 Conflicting results have been reported about household income and myopia in recently published studies. 33 , 34 Third, children from higher socioeconomic position and native Dutch children more often participate in sports than children from lower socioeconomic position and ethnic minorities in Generation R, which may result in less myopia in these groups. 12 Fourth, academic pressure from parents may be stronger in East Asian countries than in European countries as illustrated by the high prevalence of cram school attendance in East Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The data used in this study were collected from the Longhua Child Cohort Study (LCCS), which was a population-based child-caregiver cohort study among preschool children in the Longhua District of Shenzhen, China. The originally sampled participants were enrolled at the children's first entrance into kindergarten (three years old) and participated in follow-up assessments once a year (see Huang et al, 2021). The present study uses the retrospective preconception health behavior data from the baseline survey of the NETWORK OF PRECONCEPTION HEALTH BEHAVIORS 7 LCCS with a total of four cohorts included (2014 to 2017).…”
Section: Methods Participantsmentioning
confidence: 99%